Atributos do solo e modalidade de semeadura na consorciação de milho com forrageiras e desempenho agronômico do feijoeiro em sucessão - Almeida Júnior, Joaquim Júlio de [UNESP] (2015)
Facing the need of generating information for proper establishment of the integrated cattle raising-crop production system, the present work was proposed. The aim of this research was to evaluate, within an irrigated area, the methods of sowing of three species of forage in intercropping with the summer maize with straw production for the bean in succession, as well as the effects of these treatments on the soil and in the culture of maize and bean. The experiment was conducted from the year of 2012 to 2013 in the Fazenda de Ensino, Pesquisa e Extensão da UNESP/Ilha Solteira-SP, located in the county of Selvíria-MS, with 51° 22 ' longitude West of Greenwich and with 20° 22 ' South latitude, and an altitude of 335 meters. In a red dystropchic latosol clayey texture, the experimental design was established in randomized blocks with seven treatments in a factorial scheme of 3 x 2 +1 with 4 repetitions. The treatments were constituted by three forage species and two models of forage intercropping, one with the forage in the row of corn sowing with fertilization and the other with forage between the rows of corn sowing, and a witness line without intercropping. The following parameters were evaluated in the corn production: plant biometrics, and grain and straw production components. The following parameters were evaluated in the bean production: plant biometrics and component productions. In the soil were conducted chemical and physical analyses. It can be concluded that statistical differences did not occur on productivity of maize and beans with use of forages in all treatments evaluated, and the values relating to biometric characteristics and components of maize and bean production did not show statistical difference, with an exception of the average in stem diameter of corn, in which the best average obtained was for the corn intercropping with Urochloa brizantha and Pigeous Bean. Despite of not being a factor that limits or adds the ...